Arts as a Catalyst for Adult Learning - Raimundo Gaby; Welton Kwong; Elizabeth Rosini; Ramone Segree (Adult Education Research Conference, 2014)
Using collaborative inquiry, the researchers wished to explore the relationship between art and learning. Themes of individual and collective learning emerged. In general, the arts provide a useful tool for provoking reflective dialog and a platform for viewing and assuming different perspectives.